Study On The Value Of A Medium Reservoir Storage Capacity (Case Study: Karalloe Reservoir) - Widandi Soetopo; Lily Montarcih Limantara; Agustina Pagatiku (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
In this article, the value of storage capacity of a medium sized Karalloe reservoir is discussed. Together with an uncontrolled weir, the Karalloe reservoir is supplying an irrigation area. The purpose of the study is to estimate the value of reservoir storage capacity at the various storage states and at different dependable inflow levels. The Linear Programming model is used to optimize the irrigation benefit for various storage capacity and various dependable inflow levels. The results are used to estimate the values of storage capacity at various conditions. The results show that for inflow of the dry year, there is no value for the additional storage capacity. But for inflow of the wetter years, there are significant values for adding more storage capacity